Epithelial Cell Adhesion Molecule (EpCAM) Expression Can Be Modulated via NFκB - Zia, Saadiya; Tehreem, Komal; Batool, Sidra; Ishfaq, Mehreen; Mirza, Shaher Bano; Khan, Shahrukh; Almashjary, Majed N.; Hazzazi, Mohannad S.; Qanash, Husam; Shaikh, Ahmad; Baty, Roua S.; Jafri, Ibrahim; et al. (Biomedicines, 2022)
The epithelial cell adhesion molecule (EpCAM) is considered an essential proliferation signature in cancer. In the current research study, qPCR induced expression of EpCAM was noted in acute lymphoblastic leukemia (ALL) cases. Costunolide, a sesquiterpene lactone found in crepe ginger and lettuce, is a medicinal herb with anticancer properties. Expression of EpCAM and its downstream target genes (Myc and TERT) wasdownregulated upon treatment with costunolide in Jurkat cells. A significant change in the telomere length of Jurkat cells was not noted at 72 h of costunolide treatment. An in silico study revealed hydrophobic interactions between EpCAM extracellular domain and Myc bHLH with costunolide. Reduced expression of NFκB, a transcription factor of EpCAM, Myc, and TERT in costunolide-treated Jurkat cells, suggested that costunolide inhibits gene expression by targeting NFκB and its downstream targets. Overall, the study proposes that costunolide could be a promising therapeutic biomolecule for leukemia.